2015
DOI: 10.1134/s1062359015040135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype and medium culture content on microspore-derived embryo formation in Chinese cabbage (Brassica rapa ssp. chinensis) cv. Lastochka

Abstract: The influence of different factors on microspore embryogenesis in Chinese cabbage (B. rapa ssp. chinensis) was studied. A genotype dependence for embryo formation was observed. The majority of embryos and plants were obtained from microspores isolated from flower buds (2-2.9 mm in length) and cultured in the NLN liquid medium with 13% sucrose (w/v) supplemented with 24 epibrassinolide and 1% activated charcoal. Embryos cultured on the 1/2 Murashige Skoog culture medium with 2% sucrose (w/v), 0.1 mg/L benzylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…The chromosomes of the haploids can be doubled by colchicine treatment or subcluture, and the double haploids (DHs) are genetically homozygous and can be used as breeding lines directly. To date, more than hundreds of plant species have been reported and are especially widely used in Brassica crop breeding programs (Telmer, Newcomb & Simmonds, 1995;Shmykova, Shumilina & Suprunova, 2016;Shumilina, Shmykova & Bondareva, 2015). In recent years, many researchers have studied isolated microspore culture technology in Brassica and strongly improved the microspore embryogenesis rate (Yuan et al, 2011;Shumilina, Shmykova & Bondareva, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosomes of the haploids can be doubled by colchicine treatment or subcluture, and the double haploids (DHs) are genetically homozygous and can be used as breeding lines directly. To date, more than hundreds of plant species have been reported and are especially widely used in Brassica crop breeding programs (Telmer, Newcomb & Simmonds, 1995;Shmykova, Shumilina & Suprunova, 2016;Shumilina, Shmykova & Bondareva, 2015). In recent years, many researchers have studied isolated microspore culture technology in Brassica and strongly improved the microspore embryogenesis rate (Yuan et al, 2011;Shumilina, Shmykova & Bondareva, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than hundreds of plant species have been reported and are especially widely used in Brassica crop breeding programs (Telmer, Newcomb & Simmonds, 1995;Shmykova, Shumilina & Suprunova, 2016;Shumilina, Shmykova & Bondareva, 2015). In recent years, many researchers have studied isolated microspore culture technology in Brassica and strongly improved the microspore embryogenesis rate (Yuan et al, 2011;Shumilina, Shmykova & Bondareva, 2015). In particular, extensive studies have shown that pretreatment, usually performed under heat or cold treatment, is essential for Brassica embryo induction (Joosen et al, 2007;Yuan et al, 2011;Yuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Microspore embryogenesis has been described for more than 250 plant species, and efficient protocols are available for Brassica species [8]. In recent years, many researchers have studied and improved isolated microspore culture technology from genotypes, the growth environment of donor plants, microspore development stages, pretreatment conditions, plant regeneration, ploidy identification and chromosome doubling, which has improved the microspore germination rate of some of the genotypes compared to their original state [9,10]. Pretreatment is essential to embryo production, microspore and pollen isolated from cruciferous plants can produce haploid embryos in vitro without the need for intermediate callus stage under appropriate stress treatment.…”
Section: Introductionmentioning
confidence: 99%
“…В исследованиях для индукции эмбриогенеза и получения вторичных эмбриоидов активно используются разные концентрации 6-БАП в качестве регулятора роста (25). В нашей работе 6-БАП индуцировал прямой эмбриоидогенез.…”
unclassified